Unlocking barriers and strategies of halal certification for micro and small enterprises in Indonesia: Analytic network process approach - Muhammad Anwar Fathoni; Prima Dwi Priyatno; Faizi; Fadhli Suko Wiryanto; Widarto Rachbini; Suryani (Problems and Perspectives in Management)
This study aims to identify and prioritize the barriers and strategies to improve halal certification accessibility for micro and small enterprises (MSEs) in Indonesia. The paper utilized the analytic network process (ANP) to model interrelationships among barriers and strategies. Data were collected through structured interviews and surveys involving representatives from halal certification bodies (e.g., BPJPH), government agencies (e.g., DKUM Depok), and experts from academia specializing in halal certification and MSE development. The findings highlight three major barriers: financial constraints, regulatory complexities, and limited awareness among MSE owners. Financial constraints include high certification fees and costs associated with compliance. Regulatory complexities stem from the intricate procedures and bureaucratic inefficiencies in the certification process, which deter small businesses from participating. Additionally, limited awareness and understanding of halal certification’s importance and procedures exacerbate the problem, particularly among MSEs in rural or underdeveloped regions. Financial support, regulatory reforms, and educational programs emerged as the most critical strategies for overcoming these barriers. Specifically, reducing certification fees and simplifying regulatory procedures were deemed essential to increase the uptake of halal certification among MSEs. By integrating actionable insights, this study provides a roadmap for policymakers to foster a supportive ecosystem for MSEs in the halal economy. The recommendations emphasize a balanced approach that combines financial assistance, regulatory reforms, and educational initiatives to address the multifaceted barriers. This analysis contributes to the broader discourse on enhancing MSE participation in the halal market, offering implications for both local and international stakeholders seeking to optimize the halal certification process. Acknowledgment The authors would like to express their sincere gratitude to the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia (Kemendikbudristek RI) for providing financial support for this investigation. This study would not have been possible without their generous funding and commitment to advancing research in Indonesia. We also extend our appreciation to all the respondents and participants who contributed valuable insights and data for this study, as well as to the institutions involved for their support and collaboration.